Epithelial to Mesenchymal Transition as a Therapeutic Target for MicroRNAs in Triple Negative Breast Cancer - Barlev, Nikolai; Kabasheva, Aliya; Issakhanov, Darkhan (Current Medicinal Chemistry, 2026)
Breast Cancer (BC) is one of the leading causes of cancer-related deaths among females. Due to its broad heterogeneity, BC can be categorized into many subtypes, with Triple Negative Breast Cancer (TNBC) as the most aggressive one. TNBC, in addition to its unique pathophysiological features, is also characterized by specific molecular events. It is well-documented that the pathogenesis of TNBC is at least partially promoted by the process of Epithelial-to-Mesenchymal Transition (EMT). The development of EMT-associated drug resistance and metastases in TNBC patients despite chemotherapeutic treatment highlights the urgent need for the development of new treatment options. Therapeutic delivery of specific anti-tumor microRNAs is considered a promising approach for treating various forms of cancer. Analysis of the current literature suggests that EMT-suppressing microRNAs may represent a novel therapeutic treatment of breast cancer. The systemic delivery of microRNAs miR-34, miR-200, and miR-425, which specifically target the molecular drivers of EMT, showed great promise in treating TNBC in preclinical studies. However, the low specificity of systemic delivery of microRNAs <span class=
Keywords: Zeb1